Relationship of body weight with the foot shape of adult Bangladeshi male medical students: an anthropometric study - M. Tanveer Hossain Parash; Humaira Naushaba; Sadia Choudhury Shimmi (Penerbit UMS, 2015)
Foot shape significantly varies with age, sex and ethnicity. Information on gender and racial differences in foot shape is also useful to forensic scientists identifying isolated remains. Literature survey revealed that there are lot enough studies on correlation of foot shape with changes in body weight. Hence this cross-sectional and analytical study was carried out to evaluate the correlation of foot shape with changes in body weight within same race and ethnicity. A total number of 110 male medical students of 3rd and 4th year of Bengali ethnicity were chosen through purpose sampling. Foot index was calculated by dividing the foot length with the foot width. On the basis of foot index. foot shapes were classified into slender, standard and broad. Correlation of the foot shape with the body weight was assessed. Both right and left foot indices showed significant negative correlations with the body weight (r = -0.214, p: .033 and r: *0.282, p: 0.005 respectively). This approach of categorization will help in taking best fit footwear for males. It will also serve as a baseline data for forensic investigators.